PERSEPSI GURU PAMONG TERHADAP PELAKSANAAN ASISTENSI MENGAJAR MAHASISWA PGSD FKIP UNIVERSITAS QUALITY DI SDN 173404 SIRISIRISI DOLOK SANGGUL - Widiyarti, Gemala; Br Sitepu, Ganding Talia; Br Pandiangan, Elsa Juliana (Universitas Quality, 2024)
Teaching is the process of transferring knowledge from educators to students, that is the meaning that we have understood so far. However, as time goes by, the definition of teaching can be broadly interpreted as a complex activity, namely the integrative use of a number of skills to convey knowledge. Teaching assistance in educational units is a learning activity carried out by students collaboratively with teachers/tutors/facilitators/parents in various educational units in formal, non-formal and informal education subsystems. The education unit in the formal education subsystem includes the early childhood education level, namely Kindergarten-Play Group (TK-KB). The aim of this research is to see how the tutor teachers perceive the implementation of teaching assistance for PGSD FKIP Quality University students at SDN 173404 Sirisirisi. This type of research is qualitative research that uses primary and secondary data. Primary data was obtained through interviews, while secondary data was obtained through existing documents and literature studies related to student teaching assistance.